Effect of Paraquat on Tilapia Fingerlings under laboratory condition - D.K. Nkeeh; N.A. Jamabo (Journal of Applied Sciences and Environmental Management)
A total of 150 fingerlings of Tilapia guinensis, were acclimated for a period of 14days. A static bioassay was used during the period of the experiment. Mortality was measured at different time intervals of 10hr, 12hr, 16hr, 20hr, 46hr and 52hr for the range finding test, using different concentrations of paraquat (120mg/l, 60mgl, 30mg/l and 15mg/l). Acute toxicity test, using different concentrations of paraquat (10mg/l, 5mgl, 2.5mg/l and 1mg/l) was used to measure mortality of 4, 0, 0 and 0 respectively, for 96hrs. The test established the LC50 (10mg/L) of paraquat on fingerlings of T.guinensis. Three sublethal treatments (5mg/L, 2.5mg/L and 1mg/L) and five lethal treatments (120mg/L, 60mg/L, 30mg/L, 15mg/L and 10mg/L) were used during the period of the experiment. The higher the concentration (30mg/L,60mg/L and 120mg/L) of paraquat, the higher the mortality (0, 1 and 5) by the end of 10hr, thus the dose of the test chemical made the poison. Although herbicide such as paraquat can be used in the control of weed; biological and mechanical weed control methods are still better as they may pose little or no threat to the life of T. guinensis.